Tinjauan Kasus Pemerkosaan Berdasarkan Hasil Putusan PN Jayapura Dalam Perspektif Kriminologi Hukum Pidana Indonesia (Studi Kasus Putusan Nomor 139 / Pid.B / 2017 / PN Jap) - Aristias, Adinda; Andari, Astriana; Syahrani, Devy Fitri; Fatimah, Ghefira Nur; Nandita, Lufna; Rinanti, Pitra; Syawal, Zahra Auliana Putri; M, Mulyadi (Media Hukum Indonesia (MHI), 2024)
Many rape cases occur in environments that should provide a sense of security, but actually do the opposite. The term sexual violence is an unreasonable sexual act or act that can harm the victim. This research uses qualitative research methods involving analysis of legal documents and legal literature (Decision Number 139/Pid.B/2017 /PN Jap). This research uses library research to collect data. This research uses secondary data sources such as books, journals, articles and the decision of the Jayapura District Court Number 139/Pid.B/2017/PN Jap. Normative legal research is the type of research used. The results of this research show that the crime of sexual crime or rape is to satisfy the perpetrator's desires by force or not with the consent of both parties. Based on the juridical side, the criminal act of rape is seen based on existing elements, one of which is the occurrence of violence. If seen based on the decision in case Number 139 / Pid.B / 2017 / PN Jap, it is clear that this is a criminal act of rape. However, based on criminology, the benchmark is consent, not violence. These factors determine and classify the act as rape.